Pendidikan Alternatif dengan Model Pesantren Salafi-Khalafi (Studi mengenai sistem pendidikan di Komplek R2 Pondok Pesantren Al-Munawwir Krapyak) - , LITA NALA FADHILA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Pesantren (Islamic School) seen as an alternative education in the middle of weakness of formal education who maintained by the government. Because it is able to provide education for all and oriented towards the development of scientific, intellectual and intelligence character education. In its development into an alternative education, the model pesantren salafi (traditional) was criticized as too exclusive with its traditional style. On the other hand the model pesantren khalafi criticized because it has lost its identity when compromise with modernity. As an answer of criticism aimed to pesantren as education alternative, Komplek (dormitory) R2 Pondok Pesantren Al-Munawwir Krapyak Yogyakarta build pesantren with a salafi-khalafiâs model. This research focuses on the education of pesantren with the model of salafi-khalafi built on Komplek R2 by the educational system consisting of core values, the dormitory, curriculum and methods learning. Research methods uses qualitative approach by descriptive method. This research uses the technique collecting data by means of observations, an interview, study of documents and study of literature. The result showed that of core values pesantren the pray of Allah SWT with the system value namely ahl-al-sunnah wa-al-jamaâah used as basis in establishment of Komplek R2 according to pesantrenâs tradition. Dormitory or hut system applied Komplek R2 is an alternative education that creates an atmospher of kinship among pesantrenâs member. The curriculum applied in Komplek R2 is knowledge-integrated (ittihad al-ulum wa al-maârifat) that gives respect for diversity characteristic santriwati (student) because adjusted to the ability and the needs of santriwati. A method of learning applied in Komplek R2 is a method of joint salafi pesantren and khalafi pesantren complementary disadvantages of each. Education built in Komplek R2 becomes the choice an alternative for people who want to get education with tradition pesantren salafi at once tradition pesantren khalafi and education that provides equal opportunity for everyone to search of knowledge. Komplek R2 also the alternative choice for the people that not only need for education that add insight, but also intellectual education who develop morals, character and manners of the sublime. Keyword: Pesantren (Islamic Education), Alternative education, Salafi-Khalafi pesantren.